On synthesis of nanocrystalline Ti-B/Ti-B-N phases in a hypersonic plasma jet; 11th International Forum on Strategic Technology (IFOST 2016); Pt. 1 - Nikitin D. S. Dmitry Sergeevich; Sivkov A. A. Aleksandr Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich (New materials and nanotechnologies, 2016)
Title screen